Bone Tissue Engineering Strategies for Alveolar Cleft: Review of Preclinical Results and Guidelines for Future Studies - Park, Jenn J; Rochlin, Danielle H; Parsaei, Yassmin; Shetye, Pradip R; Witek, Lukasz; Leucht, Philipp; Rabbani, Piul S; Flores, Roberto L (The Cleft palate-craniofacial journal, 2023)
The current standard of care for an alveolar cleft defect is an autogenous bone graft, typically from the iliac crest. Given the limitations of alveolar bone graft surgery, such as limited supply, donor site morbidity, graft failure, and need for secondary surgery, there has been growing interest in regenerative medicine strategies to supplement and replace traditional alveolar bone grafts. Though there have been preliminary clinical studies investigating bone tissue engineering methods in human subjects, lack of consistent results as well as limitations in study design make it difficult to determine the efficacy of these interventions. As the field of bone tissue engineering is rapidly advancing, reconstructive surgeons should be aware of the preclinical studies informing these regenerative strategies. We review preclinical studies investigating bone tissue engineering strategies in large animal maxillary or mandibular defects and provide an overview of scaffolds, stem cells, and osteogenic agents applicable to tissue engineering of the alveolar cleft. An electronic search conducted in the PubMed database up to December 2021 resulted in 35 studies for inclusion in our review. Most studies showed increased bone growth with a tissue engineering construct compared to negative control. However, heterogeneity in the length of follow up, method of bone growth analysis, and inconsistent use of positive control groups make comparisons across studies difficult. Future studies should incorporate a pediatric study model specific to alveolar cleft with long-term follow up to fully characterize volumetric defect filling, cellular ingrowth, bone strength, tooth movement, and implant support.